The Effect of Liquidity, Solvency, Profitability, and Operational Costs on Corporate Income Tax in Various Industrial Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Sri Sapto Darmawati; Rosa Rosi Ana Aprogita; Ira Phajar Lestari; Bertilia Lina Kusrina; Sudaryono (Global Writing Academica Researching & Publishing, 2023)
Taxes are a source of state revenue for long-term development financing activities and regulates economic growth. One of the biggest sources of tax revenue is income tax. This study aims to examine and analyze the effect of liquidity, solvency, profitability and operating costs on corporate income tax. This study uses secondary data in the form of annual reports of various industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The number of samples used were 6 companies obtained through purposive sampling method. The results showed that partially liquidity, solvency and operational costs have an effect on corporate income tax while profitability has no effect on corporate income tax. The results of the study simultaneously show that liquidity, solvency, profitability and operational costs have an effect on corporate income tax.